THE IMPACT OF UNIVERSITY STUDENTS' PERSONAL VALUES AND MORAL COGNITION ON THEIR PERCEPTION OF SOCIAL RESPONSIBILITY - Hao Sun Hao Sun; Krittavit Bhumithavara (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
Against the backdrop of the in-depth development of globalization and informatization, where social responsibility has attracted widespread attention, and considering the significance of college students' qualities such as social responsibility—given that they are the future backbone of society—as well as the status of relevant empirical research in this field, this study takes full-time college students from Shenzhen University, South China Agricultural University, and Yanshan University as samples. It collects data through questionnaires and in-depth interviews, conducts empirical analysis using statistical tools, constructs a research framework of